Višeslojno mišljenje V. Nabokova i trenutačno zauvijek B. Pasternaka kao njihove poetičke i estetičke kategorije - Medarić, Magdalena (2000)
The paper deals with the analogy between two Russian writers concerning their ideas on time and simultaneity. Simultaneity was a widespread concept at the beginning of the twentieth century which resulted in a programme that affected numerous visual artists, poets and prose writers, especially in the early avantgarde (1910-1914). It was also a literary term (Simultaneitat, simul'tanizm, etc.) referring to devices conveying the effect of different, frequently semantically disparate, objects or events, distant from each other in space, but happening at the same time. From that point of view Vladimir Nabokov's poetics could be discussed on several levels (plot composition, parodies of contemporary literary fashion, etc.). The most interesting facet of his attitude to simultaneity is his veww of the lyrical narrator when thematized as his literary programme. In its implamentation it closely resambles Boris Pasternak's view of the lyrical subject, both in his early prose and poetry. Simultaneity has been problematized by both writers in their discursive writings as it constitutes an important element of their aesthetics. although both writers developed highly original systems, one cannot rule out a common impulse and starting point in their views of art and its relation to reality. This can possibly be due to their relatedness to the phenomenological way of thinking which was widespread and influential at that time.
Projekt MZOS
ENG